Psychological impacts, related stressor and coping strategies of the COVID-19 pandemic - Blagica R. Vanikj; Kristina Lazarevska; Aleksandra Boshkova (University American College Skopje, 2021)
This research contains eclectic analyses of the impact of the COVID 19 pandemic on the stress and anxiety level along with the findings from the in-depth empirical research that identifies the related stressors and coping strategies. This study examined and identified the COVID 19 related stressors, resilience, and family support as predictors of psychological impacts among participants that differ in age, gender, place of living, the status of living, COVID 19 status, vaccine status, education, salary, and employment. Based on the findings, the researchers identified the Coronavirus Disease 2019 related stressor, Perceived Stress and Anxiety level, Family functioning, Resilience, and Coping strategies of the participants from North Macedonia. This webbased, cross-sectional study was conducted by using the set of questionnaires based on which the quantitative analyses on the different variables have been analyzed. By computing a multivariate linear model this paper presents the results of the relevant demographic factors, coping factors, and COVID 19 stress factors that contribute to the mental health impacts during the COVID 19 pandemic. Additionally, Corona 19 related stressors and coping factors were confirmed as predictors of psychological impacts identified by multiple regression analyses. The paper increases the knowledge of mental health professionals and the wider population in identifying risk factors and symptoms of mental stress, distress, and disorder from COVID 19 for better identification and management of the client's treatment. This practical approach should increase the awareness of the people about the importance of seeking support, mental health facilitation as well as counseling and psychotherapeutic services during pandemic situations. Reliable information, accessible services, and stronger collaboration between academic institutions, clinical work, and public health can be a suitable approach for mental health issues prevention and taking appropriate measures for coping with the psychological impacts on a long-term basis.
Keywords: 330; stress; anxiety; COVID-19; resilience; coping strategies